Nitrogen Sorptiometric Study of Phosphation and Dispersion of Lanthanum(III) Oxide on Alumina Catalysts - Gamal A.H. Mekhemer; Ali F. Bukhzam; Amal S. El-Towaty; Mohamed I. Zaki (Adsorption Science & Technology)
Alumina-supported lanthanum(III) oxide catalysts at loadings varying in the range 3–30 wt% La 2 O 3 were prepared by wet impregnation and calcination at 920 K for 2 h. An analogous series of catalysts were phosphated by impregnation with up to 6 wt% PO 4 3– from aqueous solutions of (NH 4 )H 2 PO 4 and then calcined similarly. The catalysts thus obtained were characterized by X-ray diffractometry, infrared spectroscopy and nitrogen sorptiometry at 77 K. The adsorption data were analyzed by the BET method and the t-method. The results suggested that lanthanum(III) oxide loadings up to 30 wt% exist as high-dispersion two- and three-dimensional structures on the surface of alumina that are not XRD-detectable (particle size < 2 nm). Strong interactions not only at the liquid/solid interface established during impregnation, but also at the solid/solid interface established during drying and/or calcination, are suggested to be important events in the dispersion mechanism. Phosphation led to the improvement of the two-dimensional lanthanum(III) oxide dispersion (probably in monolayers) rather than the three-dimensional one, most likely through direct bonding of the phosphate groups to exposed La 3+ sites. It is inferred that nitrogen adsorption data can provide valuable qualitative information on the dispersion of supported oxide materials.